Anomalous Origin of the Left Coronary Artery from the Pulmonary Artery Diagnosed in Adulthood - Xie, Nanai; Liu, Jingyan; Zhang, Heng; Zhu, Yuhui; Ma, Wanling (Current Medical Imaging, 2024)
Introduction An anomalous left coronary artery from the pulmonary artery (ALCAPA) is a rare heart malformation, with 90% of patients dying during the first year of life. If the right coronary artery compensation and multiple collateral circulation are sufficiently established, the patient's myocardial ischemia symptoms are mild and appear later, which is called the adult type ALCAPA. Case Description A 42-year-old woman presented to our hospital with one-month history of the aggravation of active shortness of breath which gradually progressed to nocturnal paroxysmal shortness of breath and cough. Admission physical examination suggested mild edema of both lower limbs. Transthoracic echocardiography (TTE) showed that a small vessel shadow was abnormally connected to the pulmonary artery (PA), and moderate pulmonary artery hypertension. Coronary computed tomography angiography (CTA) showed an anomalous origin of the left main coronary artery (LMCA) dividing into the left anterior descending (LAD) and left circumflex (LCX) artery from the PA, with no clear connection to the left coronary sinus. The right coronary artery (RCA) was significantly dilated and originated from the normal Valsalva sinus. It was accompanied by multiple collateral circulations, most of which traveled anterior to the right ventricular free wall and anterior interventricular sulcus, and some emanated from the posterior descending branch of the posterior interventricular sulcus and walked toward the posterolateral wall of the left ventricle. Conclusion Coronary computed tomography angiography (CTA) can be used to visualize the abnormal origin and distribution of the coronary artery's course and may be the first choice in the diagnosis of ALCAPA.
Keywords: An anomalous left coronary artery from the pulmonary artery